PRODUCTIVITY GOAT LAKOR FARMING ON LAKOR ISLAND SOUTHWEST MALUKU DISTRICT - Tanody, Wisye; Joseph, Godlief; Rehatta, Lea Marylin (RUMPHIUS, 2023)
This study aims to determine the productivity of Lakor goats in rural conditions on Lakor Island, Southwest Maluku Regency. This researchwas conducted in October-November 2022 on Lakor Island. This research used This study used 60 Lakor goat breeders as respondents and the design. The results of this study showed that the average birth weight was 1kg, weaning weight was 13,15kg, bodyweight for kid goats aged 1-2 years was 86,91-22,84kg, number of matings 1,5-3 times, type of birth from a single sample village 11,32, twins 42,14, triplets 19,93, litter size 1,97, pre-weaning motility 7,33, sex ratio 3,31-3,70 and estrus cycle 18-24 days. It can be concluded that the productivity of Lakor goats in rural conditions in Pulau Lakor, West Maluku districtthe power is very good because even though the rearing of goats on Lakor Island is semi- intensive, green feed on Lakor Island really meets the needs of livestock so as to produce ideal body weight.